Effects of neurofeedback training on frontal midline theta power, shooting performance and attentional focus with experienced biathletes - McGawley, K.; Toolis, T.; Laaksonen, M. S.; Cooke, A. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Frontal midline theta power (FMT) has previously been associated with superior rifle shooting performance 1, which is crucial for successful biathlon performance 2,3. The purpose of the present study was to identify whether neurofeedback training using electroencephalography (EEG) would lead to increased FMT and improved rifle shooting performance and attentional focus in biathletes.